NITRIFYING AND PATHOGENIC BACTERIAL FLUCTUATION DURING NITROGEN REMOVAL FROM WASTEWATER IN ZAKHO CITY/IRAQ - Mohammed, Khawla A.; Umer , Mustafa I.; Alyazichi , Yasir M. (Science Journal of University of Zakho, 2023)
The high concentration of nitrogen (N) compounds in wastewater was found to be creating a reason of eutrophication, effect the biodiversity of aquatic ecosystems and human health. The aim of this study is to reduce harmful N forms from wastewater by biological nitrogen transforming (BNT) bacteria and to investigate the fluctuation of ammonium oxidizing bacteria (AOB), nitrite oxidizing bacteria (NOB), and pathogenic bacteria during this process, so compost representative. A sample of municipal wastewater was taken, and then subjected to the treatment process of BNT, which was subdivided into three stages of ammonification, nitrification, and denitrification. The result revealed that nitrifying bacteria were flocculated during biological nitrogen transformation, like AOB and NOB isolated until obtaining colonies during the nitrification process, by liquid mineral solution and Agar-Agar then calculated. The AOB count was 468 CFU/ml and NOB was 2130 CFU/ml in the sample. The existence of coliform bacteria, especially E. coli raises the possibility of water contamination by pathogens bacteria that cause many serious illnesses in human. Therefore, Mac-Conkey agar was used for the isolation of total coliform bacteria through the BNT process because it is selective and also differentiating agar that specialized in the growth of gram- negative bacteria. Total coliform bacteria decreased gradually, before ammonification (556 CFU/ml), after ammonification (226 CFU/ml), after nitrification (154 CFU/ml) and after denitrification (45 CFU/ml) that have been determined and indicated that further chemical disinfection like chlorination or ozonation were required for complete sterilization of pathogenic bacteria. The study concluded that all harmful forms of N and total coliform bacteria that cause human and ecosystem deleterious were reduced by BNT.
Keywords: Biological nitrogen transformation; NOB; Coliform Bacteria; AOB